Fondaparinux versus enoxaparin in the management of acute coronary syndromes in Switzerland (Swiss Medical Weekly, 2012)
QUESTION UNDER STUDY: Anticoagulation therapy is routinely used in cases of non ST-segment elevation acute coronary syndromes (NSTE-ACS). The most commonly used drug in such events is enoxaparin, a low molecular weight heparin. Fondaparinux, a synthetic pentasaccharide, is as effective as enoxaparin in terms of survival or residual angina pectoris and significantly reduces bleeding complications. The purpose of this study was to assess the magnitude of cost reductions if enoxaparin were replaced by fondaparinux in Switzerland. METHODS: Costs of hospital stay for NSTE-ACS with or without bleeding complications at the Geneva University Hospitals were determined for patients admitted between July 1st, 2007 and June 30th, 2008. These costs were applied to subjects recruited in the AMIS Plus registry, which gathers information on ACS in Swiss hospitals, using three scenarios. Firstly, using the baseline incidence of bleeding episodes observed in the AMIS plus registry. Secondly, using the baseline incidence of haemorrhagic episodes observed in the Geneva University Hospitals sample and thirdly, using the incidence of haemorrhagic episodes observed in the OASIS-5 study. These results and costs were then extrapolated to the national level. RESULTS: At the Swiss national level, replacement of enoxaparin by fondaparinux would generate annual savings ranging from 854,000 Swiss Francs (scenario 1) to 3,400,000 Swiss Francs (scenario 2) and 2,845,000 Swiss Francs (scenario 3). Estimated savings accounted for 55 to 63% of total hospital costs. CONCLUSIONS: Use of fondaparinux instead of enoxaparin in patients with NSTE-ACS could yield substantial savings at the local as well as the national level in Switzerland.